Hemangioma of the rib showing a relatively high 18F-FDG uptake: a case report with a literature review. (September 2017) - Itabashi, Takahide; Emori, Makoto; Terashima, Yoshinori; Hasegawa, Tadashi; Shimizu, Junya; Nagoya, Satoshi; Yamashita, Toshihiko
Hemangioma of the rib is a rare benign tumor that is often difficult to distinguish from malignant bone tumors. Rib hemangioma often shows bony disruption with a slight cortical disruption, extraosseous lesion, and expanded bone on computed tomography (CT). We report the case of a 68-year-old man with atypical rib hemangioma with a slight cortical disruption and no expanded bone. The tumor showed relatively high 18FDG-uptake on positron emission tomography (PET)/CT. Rib hemangioma often shows higher 18FDG-uptake. PET/CT may not provide useful information for distinguishing rib hemangioma from a malignant tumor. Close observation without surgical resection may be feasible if the tumor is diagnosed as a rib hemangioma by biopsy.